Coagulopathy and Antiphospholipid Antibodies in Patients with Covid-19 - Zhang, Yan; Xiao, Meng; Zhang, Shulan; Xia, Peng; Cao, Wei; Jiang, Wei; Chen, Huan; Ding, Xin; Zhao, Hua; Zhang, Hongmin; Wang, Chunyao; Zhao, Jing; et al. (The New England journal of medicine, 2020)
The authors describe a 69-year-old man with Covid-19 diagnosed in January 2020 in Wuhan, China, along with two other critically ill patients with Covid-19 who were also seen in the same intensive care unit. Coagulopathy and antiphospholipid antibodies were seen in all three patients.